Harvest and postharvest Physicochemical characteristics of three selected Saba Banana (Musa Balbisiana Cv. Saba) accessions In Sabah - Ser, Li Yun (Universiti Malaysia Sabah, 2017)
The study was carried out in the Postharvest laboratory of Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, campus Sandakan from 15th July 2016 until 15th September, 2016 to evaluate the standard quality of harvest and postharvest physical and chemical characteristic of three selected Saba banana accessions collected from three different district of Sabah (which were Sandakan, Keningau and Kata Marudu). The experiment was conducted in a Completely Randomized Design (CRD) with four replications from the three accessions based on maturity indices for each individual analysis test (3 X 8 X 4). Fruit characteristics of Saba banana at harvest including mean weight of banana hand, number of fingers per hand, volume of finger, geometric mean diameter, sphericity, and aspect ratio were analysed by using One-Way Analysis of Variance (ANOVA). Postharvest physical and chemical characteristics changes of Saba banana which were changes in weight loss percentage (WLP), pulp to peel ratio (g/g), pulp firmness (kgF), visual appearances {VA), degree of browning (DOB), pulp and peel colour in terms of lightness (L *), chroma (C*) and hue angel (h0) value, total soluble solid (TSS), pH value, titratable acidity {TA), pulp and peel moisture content (MC), and rate of filtration (ROF) were subjected to two-way ANOVA at 5% level of significance. The study rejected Ho whereby the harvest and postharvest physical and chemical characteristics of three selected Saba banana accessions in Sabah have a significant differences. The result shown that postharvest characteristics at harvest of Saba banana from each accessions were significant differences except number of fingers per hand. Both the weight of banana per hand and volume of finger of Saba banana from Kata Marudu was the highest as compared to other accessions. The extracted data shows significant differences in physical and chemical characteristics on a daily basis with passage of maturity stage. The most useful and reliable maturity indices for banana fruits of Saba variety were firmness, peel colour and total soluble solid content. The investigation can be helpful to process industry since the selection of fruit with optimum value of respective physicochemical property can yield the product with good quality. The physicochemical characteristics evaluated in this study can be important postharvest quality criteria for the processing, screening and breeding of Saba banana. Similar studies on the influence of climate and farmer's cultural practice can be done for further ascertain the changes in postharvest physical and chemical characteristics of Saba banana in Sabah.